Engineering State‐of‐the‐Art Plasmonic Nanomaterials for SERS‐Based Clinical Liquid Biopsy Applications. Issue 23 (30th September 2019) - Wang, Jing; Koo, Kevin M.; Wang, Yuling; Trau, Matt
Abstract: Precision oncology, defined as the use of the molecular understanding of cancer to implement personalized patient treatment, is currently at the heart of revolutionizing oncology practice. Due to the need for repeated molecular tumor analyses in facilitating precision oncology, liquid biopsies, which involve the detection of noninvasive cancer biomarkers in circulation, may be a critical key. Yet, existing liquid biopsy analysis technologies are still undergoing an evolution to address the challenges of analyzing trace quantities of circulating tumor biomarkers reliably and cost effectively. Consequently, the recent emergence of cutting‐edge plasmonic nanomaterials represents a paradigm shift in harnessing the unique merits of surface‐enhanced Raman scattering (SERS) biosensing platforms for clinical liquid biopsy applications. Herein, an expansive review on the design/synthesis of a new generation of diverse plasmonic nanomaterials, and an updated evaluation of their demonstrated SERS‐based uses in liquid biopsies, such as circulating tumor cells, tumor‐derived extracellular vesicles, as well as circulating cancer proteins, and tumor nucleic acids is presented. Existing challenges impeding the clinical translation of plasmonic nanomaterials for SERS‐based liquid biopsy applications are also identified, and outlooks and insights into advancing this rapidly growing field for practical patient use are provided. Abstract : In a bid to facilitate next‐generation plasmonic nanomaterials for clinical exploration of SERS‐based liquid biopsy applications, a detailed overview of up‐to‐date plasmonic nanomaterials that are designed for SERS applications and newly developed SERS technologies for liquid biopsies, is provided.